If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(c + 15) + (-1) = -9 Reorder the terms: -4(15 + c) + (-1) = -9 (15 * -4 + c * -4) + (-1) = -9 (-60 + -4c) + (-1) = -9 -60 + -4c + -1 = -9 Reorder the terms: -60 + -1 + -4c = -9 Combine like terms: -60 + -1 = -61 -61 + -4c = -9 Solving -61 + -4c = -9 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '61' to each side of the equation. -61 + 61 + -4c = -9 + 61 Combine like terms: -61 + 61 = 0 0 + -4c = -9 + 61 -4c = -9 + 61 Combine like terms: -9 + 61 = 52 -4c = 52 Divide each side by '-4'. c = -13 Simplifying c = -13
| -2a=3s-10 | | -8y-2=-7y-6 | | 38=22-(8-6t) | | 3/4x5/7 | | (28b-1)-9(3b+1)=-2 | | 19x+4+26x-4=180 | | y/4-6=-9 | | 12-4(2x+3y)= | | 6/d=3 | | 8v-5+1=-4 | | 240-83x=541 | | 3x+41-5x=3-8x+2 | | 1/4x+1/4x=8 | | k+4(2k-7)=-100 | | (3/4)/(5/7) | | 2-5p-3p=-6 | | 3/4/5/7 | | -2m-24=0 | | 2-5p-4p=-6 | | 48/60 | | y+1=6/5x+18/5 | | a+4+2a=-8 | | -8n+-4=-28 | | (-3)*(-13)+(-41)= | | -11+2(x-3)+x=3(x-3)-8 | | 1=2+1/2 | | 5(3x+2)=2(2x+3) | | 5(x-2)-3=2x+3(-3+x) | | -5(7+7n)=-280 | | x/2+6=3x-12+x/2 | | 12x+15=-2 | | 3x+7=6x+9 |